2019
DOI: 10.1177/1747021818821601
|View full text |Cite
|
Sign up to set email alerts
|

The contributions of language control to executive functions: From the perspective of bilingual comprehension

Abstract: Previous studies have suggested that bilingual production experience has beneficial effects on executive functions. In the current study, four experiments were conducted to investigate whether bilingual comprehension experience influences executive functions. In Experiments 1 and 2, Chinese–English bilinguals completed a flanker task interleaved with a language comprehension task (reading comprehension in Experiment 1 and listening comprehension in Experiment 2). There were three blocks distinguished by langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 35 publications
4
36
0
Order By: Relevance
“…Moreover, several studies have suggested that the language context can modulate executive control. Jiao, Liu, Liang, et al (2019) examined how the language context modulated the executive control system. A group of bilinguals performed a flanker task interleaved with a picture-word matching task, which was used to create single-language (all words presented in the same language) and mixed-language (words presented interchangeably in two languages) contexts.…”
Section: The Role Of Language Contextmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, several studies have suggested that the language context can modulate executive control. Jiao, Liu, Liang, et al (2019) examined how the language context modulated the executive control system. A group of bilinguals performed a flanker task interleaved with a picture-word matching task, which was used to create single-language (all words presented in the same language) and mixed-language (words presented interchangeably in two languages) contexts.…”
Section: The Role Of Language Contextmentioning
confidence: 99%
“…The flanker task was used to measure executive control and included congruent and incongruent trials (Dong & Zhong, 2017;Jiao et al, 2019aJiao et al, , 2020Wu & Thierry, 2013). Based on relevant studies (Jiao, Liu, Liang, et al, 2019), we speculated that the language context would affect behavioral performance during the flanker task, with shorter flanker RTs in the mixed-language context than in single-language contexts. Moreover, we expected that the effect of language context would be observed in both congruent and incongruent flanker trials in behavioral performance.…”
Section: The Present Studymentioning
confidence: 99%
See 3 more Smart Citations